Limitations on Cigarette Purchasing as a Solution to Reducing the Prevalence of Smoking in Indonesia - Raodatul Jannah (Syntax Idea)
Cigarettes are processed tobacco products, including cigars or other forms. Results of the Global Adult Tobacco Survey (GATS) in 2021 shows that Indonesia has the highest number of male smokers in the world and the third largest number of smokers in the world after India and China. During 2012-2022 Indonesian government will increase the Tobacco Products Duty almost every year to reduce the growth rate of smokers as well as provide income to the state treasury. However, the suppress still not optimal enough as a result of estimated state spending, especially for health care due to smoking, which exceeds state income from cigarettes and tobacco. This paper examines ad blocking and restrictions on purchasing cigarettes as a solution to reducing smoking prevalence in Indonesia. This paper applies descriptive qualitative methods and netnography methods that the researchers carried out by means of observations on YouTube social media as well as field observations in the city of Semarang, as well as online interviews using the WhatsApp application media with cigarette sellers in the city of Semarang as informants. This paper shows that cigarette advertising is very influential in increasing the number of smokers, especially among child smokers. The implementation of the smoking ban which has been regulated in Government Regulation Number 109/2012 concerning Safeguarding Substances Containing Addictive Tobacco Products for Health is also considered less than optimal. The implications of this finding both demand and encourage the government to be able to immediately issue regulations in order to block advertisements and at the same time control and limit the sale of cigarettes to children and/or youth in a systematic way, for example by utilizing the PeduliLindungi application which is considered quite successful in controlling the COVID-19 pandemic. in the past 2020-2021.